Longitudinal changes in placental biomarkers in women with early versus late placental dysfunction - Manouk L. E. Hendrix; Kirsten C. M. Palm; Sander M. J. Van Kuijk; Otto Bekers; Marc E. A. Spaanderman; Judith A. P. Bons; Salwan Al-Nasiry (Taylor & Francis Group, 2019)
Objective: To evaluate longitudinal changes of angiogenic biomarkers in early- (EO-PD) versus late-onset (LO-PD) placental dysfunction. Methods: Serum PlGF and sFlt-1 measured at different intervals in EO-PD (n= 43), LO-PD (n= 31) and controls (n = 133). Results: sFlt-1/PlGF ratio was higher at 16 weeks (30.6 vs 17.5), 20 weeks (29.3 vs 8.9) and 30 weeks (16.6 vs 6.7) in EO-PD vs controls (all p< 0.05), but not in LO-PD. Longitudinal changes for all intervals had higher AUC than single measurements. Conclusion: Longitudinal biomarker change between 12 and 30 weeks could improve prediction of EO-PD compared to single measurements.